Critically ill patients with necrotizing soft tissue infections in the Caribbean area: unsupervised analysis of a retrospective cohort (2014–2023) with identification of factors associated with mortality - Jean-David Pommier; Benoît Tressieres; Pascal Blanchet; Frederic Desmoulins; Pascale Piednoir; Nejla Aissa; Frederic Martino; Marc Valette; Alexandre Demoule; Sebastien Breurec; Laurent Camous (Annals of Intensive Care)
Abstract Background Scarce epidemiological data are available regarding necrotizing soft tissue infections (NSTIs) in tropical areas. Here we aimed to describe the clinical and biological features, and outcomes, of critically ill patients with NSTIs admitted to an intensive care unit (ICU) in a tropical setting. Furthermore, we analyzed these findings to identify distinct clinical phenotypes and explore their associations with patient outcomes. Methods This retrospective observational study included all patients with NSTIs admitted to the ICU of the University Hospital of Guadeloupe between January 2014 and December 2023. Subgroups of patients having similar clinical profiles were identified through unsupervised clustering (factor analysis for mixed data, and hierarchical clustering on principal components). Univariate and multivariate analyses identified factors associated with 90-day mortality. Results During the study period, 91 NSTI patients were admitted to the ICU. The median Simplified Acute Physiology Score (SAPS) II was 45 [IQR 40–66], and the median time between hospital admission and first surgical debridement was 8 h [IQR 6–10 h]. While in the ICU, 65% of patients were mechanically ventilated, 75% experienced shock, and 34% underwent renal replacement therapy. The 90-day mortality rate was 32%. Unsupervised clustering revealed three clusters—mild NSTI (n = 23, 25%), severe NSTI (n = 49, 54%), and fulminant NSTI (n = 19, 21%)—which were associated with different ICU courses and outcomes. Subcutaneous emphysema and sepsis-associated encephalopathy were key components influencing cluster identification. Multivariate analysis revealed that mortality was associated with SAPS II, subcutaneous emphysema, >8 h between hospital admission and first surgery, and immunocompromised status. Conclusion Unsupervised analysis of critically ill patients with NSTIs in tropical settings revealed three distinct patient clusters that exhibited unique phenotypic characteristics and clinical outcomes. Upon hospital admission, patients with NSTIs should be carefully screened for sepsis-associated encephalopathy, subcutaneous emphysema, and thrombopenia. The present exploratory results must be confirmed in larger multicentric cohorts.